Does Effleurage Massage Reduce Dysmenorrhoea Pain in Adolescents? - Sumiaty, Sumiaty; Nurfatimah, Nurfatimah; Sartika, Yuni; Ramadhan, Kadar (JURNAL INFO KESEHATAN, 2023)
Dysmenorrhea, commonly known as menstrual pain or cramps, affects some women and hampers their ability to carry out daily activities. In Indonesia, the incidence of dysmenorrhea among women is reported to be 64.25%, with a significant proportion lacking knowledge regarding its management. Non-pharmacological methods, such as effleurage massage, have been suggested as a viable approach to alleviate dysmenorrhea pain. This study aimed to investigate the impact of effleurage massage on the pain scale associated with dysmenorrhea in adolescents. A quasi-experimental approach utilizing a pre- and post-test for a two-group design was employed. The study population consisted of young women experiencing dysmenorrhea, with a total sample size of 44 respondents divided into intervention and control groups. The research findings revealed a decrease in the mean pain score in the intervention group from 5.1±2.4 to 2.5±1.8 with a p-value of <0.001. Thus, it can be concluded that effleurage massage effectively reduces the intensity of dysmenorrhea pain in adolescents. As a recommendation, adolescents are advised to consider non-pharmacological therapies like effleurage massage as an alternative to pharmacological drugs, and to learn the technique to perform effleurage massage independently at home.